The influence of hand guards on explosive force and pain and exertion perception in a hang holding task - Santos Júnior, J. L. N.; da Silva Passos, R.; Alves Oliveira, A.; Dias da Silva, J. R.; Silva Souza, R.; da Silva Passos, R.; Machado, M.; Koch, A. J.; Pereira, R. (Science of Gymnastics Journal, 2021)
We investigated whether hand guards (HG) influence the perception of pain and exertion during the execution of a standardized task on high bar to induce forearm muscle fatigue as well as a decline in grip strength after the task. Design: A cross-over study design was employed 15 healthy and physically active volunteers completed static bodyweight holds (8 cycles of 20 second load in hang and 10 second rest), on a high bar. The exercise protocol was performed with and without HG. Perception of pain and exertion during the task were recorded. Peak handgrip force and explosive force parameters (i.e., rate of force development [RFD] and contractile impulse [CI] at 30 to 200 ms) were obtained from force-time curves. Peak force and explosive force parameters were normalized (i.e., POS/PRE) for statistical analysis. The use of a HG significantly attenuates pain perception (p < 0.05), with a moderate to large effect size (d = 0.52), but did not alter the perception of exertion during the task, nor did it alter peak force, RFD, or CI. The use of HG reduces the perception of local pain during static holds. However, HG do not alter the perception of exertion during the task nor do they alter the gripping force ability immediately afterwards. This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors.